2020
DOI: 10.1021/acs.langmuir.0c01493
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation of Surfactant-Free Emulsion Polymerization Using Magnetite Nanoparticles Modified by Citric Acid as Stabilizers

Abstract: Fe3O4-armored latexes were successfully synthesized by using modified Fe3O4 (IO) nanoparticles as stabilizers without a surfactant. The particle size, conversion, and particle number density of latex particles during the formation process were studied in detail. The surface charge density and the particle size evolutions of latexes were studied by dynamic light scattering. The use of scanning electron microscopy confirmed that IO nanoparticles were adsorbed on the polymer particle surface. Furthermore, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 46 publications
2
7
0
Order By: Relevance
“…In addition, the synthesis requires only a minimum number of ingredients, and, in particular, no molecular surfactant is left in the suspension (at the inorganic surface or in the solution), making this method a valuable approach for the design of new and highly performant materials. Despite the surge of interest in the use of inorganic particles as solid stabilizers of surfactant-free emulsion polymerization processes, only a little attention has been paid to IO particles. Xu et al reported the successful formation of magnetic polystyrene microspheres using 2,2′-azobis­(2-methylpropionamide) dihydrochloride (V50) as a cationic initiator and poly­(methacrylic acid) (PMAA)-functionalized IO nanoparticles as a Pickering stabilizer. The electrostatic interaction between the amidine group of V50 and the carboxylate anions of PMAA under basic conditions was key in obtaining stable composite particles with the targeted raspberry-like morphology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the synthesis requires only a minimum number of ingredients, and, in particular, no molecular surfactant is left in the suspension (at the inorganic surface or in the solution), making this method a valuable approach for the design of new and highly performant materials. Despite the surge of interest in the use of inorganic particles as solid stabilizers of surfactant-free emulsion polymerization processes, only a little attention has been paid to IO particles. Xu et al reported the successful formation of magnetic polystyrene microspheres using 2,2′-azobis­(2-methylpropionamide) dihydrochloride (V50) as a cationic initiator and poly­(methacrylic acid) (PMAA)-functionalized IO nanoparticles as a Pickering stabilizer. The electrostatic interaction between the amidine group of V50 and the carboxylate anions of PMAA under basic conditions was key in obtaining stable composite particles with the targeted raspberry-like morphology.…”
Section: Introductionmentioning
confidence: 99%
“…The suspension pH was also shown to be a key parameter, influencing the interaction of the auxiliary comonomer with the IO surface and hence the incorporation efficiency. More recently, the approach was extended to citric-acid-functionalized IO particles, combined with the use of a cationic initiator, thereby eliminating the need for auxiliary comonomers . In both cases, a detailed mechanistic investigation of particle formation revealed a complex interplay between IO and latex colloidal stability resulting in small composite latex particles, with in the best case a 90% IO incorporation efficiency, with, however, an irregular and relatively low surface coverage of less than 35%.…”
Section: Introductionmentioning
confidence: 99%
“…Armored particles have a polymer core coated with inorganic nanoparticles; such armored particles can be used as feedstocks for composite structures. These particles can be prepared by dispersion polymerization of the discontinuous phase of Pickering emulsions or by the deposition of inorganic particles onto preformed polymer particles. Two-dimensional (2D) nanosheets, including graphene oxide (GO) nanosheets and clay platelets, have been widely used to prepare armored particles, most commonly by the dispersion polymerization method. For example, the Pentzer group demonstrated the preparation of armored particles using oil-in-water emulsions stabilized by GO and UV-initiated thiol-ene polyaddition polymerization of the oil phase. The same group used oil-in-oil emulsions stabilized by alkylated GO and thermally initiated free-radical polymerization of a methacrylate monomer as the discontinuous phase to prepare armored particles. , In a similar vein, Zhang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, in 2020, K. Li et al [ 20 ] successfully prepared a stable nanocomposite emulsion that can be obtained by magnetite nanoparticle (pre‐modified with citric acid) (IO) as a solid stabilizer without using any auxiliary monomers via surfactant‐freeemulsion polymerization. The particle nucleation followed the homogeneous nucleation mechanism, in which the initiator decomposed producing the free radicals.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, numerous researchers focused on magnetic iron oxide nanoparticles such as carbonyl iron, Fe 2 O 3 , and Fe 3 O 4 as stabilizing particles due to their potential features. [ 11,20‐30 ] On the other hand, polystyrene, as a polymer matrix, has been gained attention in numerous studies because of its well‐known structure system as its chains can be generated by polymerizing the respective monomer in the presence of nanoparticles. [ 27,31 ] Our group successfully prepared stable o/w emulsions of styrene as a monomer in water via Pickering emulsification using silica, [ 14 ] montmorillonite, [ 5 ] and laponite (RD) [ 32 ] nanoparticles as stabilizers compared to conventional surfactants, where the resulting solid stabilized o/w emulsions displayed outstanding stability against coalescence as well as coagulation.…”
Section: Introductionmentioning
confidence: 99%